Comparisons of water- and land-based physical activity interventions in Japanese subjects with metabolic syndrome - Hanai, A.; Yamatsu, K. (Biomechanics and Medicine in Swimming XI, 2010)
We previously reported that group-based physical activity (PA) intervention had beneficial effects on weight loss in Japanese subjects with metabolic syndrome (MS). Although, water- and land-based PA intervention was often conducted, it is unknown which PA interventions were more effective. The aim of this study was to compare the efficacy of these two interventions in Japanese subjects with MS or several MS risk factors (such as overweight, diabetes, hyperlipidemia). As a result, after 10-weeks, participants in both groups reported significant loss of weight, BMI, and percent body fat. Statistical analyses showed no significant differences between the groups with the exception of daily physical activity levels. It was suggested that both water- and landbased physical activity interventions had short-term beneficial effects on weight loss and reduction of percent body fat.